Adolescents' Utilization of a Tertiary-Level Pediatric Emergency Department in Italy - Cozzi, Giorgio; Passaglia, Lisa; Agrusti, Anna; Giangreco, Manuela; Giorgi, Rita; Barbi, Egidio (Frontiers in Pediatrics, 2022)
Aim Describe the use of the emergency department of a tertiary-level children's hospital in Italy by adolescents. Methods This retrospective study was based on the medical records of patients aged 13 to 17 years, who accessed the emergency department of the Institute for Maternal and Child Health of Trieste, from 1 January to 31 December 2018. The primary outcome was to describe the leading causes of access, diagnoses, rate of hospitalization, and ward of destination among adolescent patients. Results During the study period, 24,599 patients accessed the department. Among them, 3,062 were adolescents, for a total of 3,895 unscheduled visits. The principal causes of access were trauma (45.3%) and organic diseases (38.8%). Two hundred and forty nine adolescents (6.4%) had mental health problems. One hundred and forty two adolescents (3.6%) Were Admitted to the Hospital, 54 of Whom (38%) to the Neuropsychiatric Ward, for Mental Health Problems. Conclusions Among adolescents seen in this Italian tertiary-level children's hospital, mental health problems represented a small proportion of emergency department visits but were the leading cause of urgent hospitalization.